Planning and developing advisory programs for the personalization of education: a handbook to guide school leaders of large high schools in Kansas - McCarty, Terrell Dwayne (Kansas State University, 2014)
The purpose of this study was to research and create a comprehensive handbook for planning and developing advisory programs for the personalization of education. This is known as personalized learning. Personalized learning refers to the structures, policies, and practices that promote relationships based on mutual respect, trust, collaboration, and support (Breunlin, Mann, Kelly, Cimmarusti, Dunne, & Lieber, 2005). Planning and Developing Advisory Programs for the Personalization of Education: A Handbook to Guide School Leaders of Large High Schools in Kansas was developed using the research and development methodology (R & D) developed by Gall and Borg (Gall, Borg, & Gall, 2007). A prototype of the handbook was developed and then evaluated by experts in the area of the personalization of education. A Preliminary Field Test was electronically sent to all building principals of high schools in Kansas with student populations of 1000 students or more. Revisions were made to the handbook based on feedback received. The revised handbook was then distributed to three professionals, nominated by their peers, for the main field test. Feedback from the main field test was used to create the final product. The conclusions from the research project indicated: (1) there is a strong need for administrators and educators to personalize the learning environment through advisory programs; (2) large high schools were in need of a resource that was relevant in their respective schools; (3) the need for a handbook such as this to address key components such as transition, support interventions, and academic counseling; and (4) that a comprehensive handbook that included a step-by-step process, discussing critical components for administrators on how to personalize education utilizing advisory programs could address numerous concerns in large high school.
Keywords: Personalization; Advisory programs; Transition; High schools; Handbook; Planning; Educational leadership (0449); Education, General (0515); Secondary Education (0533)